Factors Determinants of Musculoskeletal Disorders among Nurses in Indonesia: Evidence from A Cross-Sectional Study - Suryani, Lilis; Perdani, Agni Laili; Al Freadman Koa, Apryadno Jose (Universitas Pendidikan Indonesia, 2025)
Introduction: Musculoskeletal disorders (MSDs) remain a significant occupational health issue among nurses, influenced by demographic factors, workload, stress, and ergonomic posture. Nurses are particularly vulnerable due to heavy physical demands, non-ergonomic postures, and psychosocial pressures. Objective: This study aimed to determine factors that contribute to MSDs among nurses in Indonesia. Methods: A quantitative descriptive design was employed with a convenience sampling method. Data were collected from nurses in a one-month period in September–October 2024. Four validated instruments were used consisting of the Nordic Musculoskeletal Questionnaire (NMQ), the NASA Task Load Index (NASA-TLX), REBA (Rapid Entire Body Assessment) and HSE (Health and Safety Executive). Health Data was analyzed using bivariate (ANOVA) with SPSS Version 25. Results: A total of 108 participants agreed to participate in this study. The majority of respondents were aged 26–45 years (67.6%), and most were female. Findings revealed a significant relationship between work burden, work stress, and work duration with MSDs. Conclusion: Factors contributing to MSDs among nurses are work burden, work stress and work duration with MSDs. Hospital management should implement workload evaluations, shift management, and ergonomic training, while the nursing profession should strengthen awareness of proper working postures, physical health maintenance, and stress management strategies.